Mechanisms of hemodialysis and peritoneal dialysis (Research, Society and Development, 2022)
Dialysis is a treatment that replaces some of the kidney functions, such as elimination of fluids, acid-base control, elimination of potassium and protein metabolism residues. Dialysis treatment is medicated with erythropoietin and vitamin supplementation. There are two types of dialysis: hemodialysis, where the patient's blood is filtered by a machine called a dialyzer, which is where ultrafiltration and blood diffusion occurs; and peritoneal dialysis that uses the peritoneum, a semipermeable membrane located in the abdomen that filters blood effectively. Renal failure that can lead to dialysis treatments can be identified from some laboratory tests such as: urea, creatinine, glomerular filtration rate, creatinine clearance, cystatin C, abnormal urinary sediment elements and renal biopsies. Aiming to understand the mechanisms of hemodialysis and peritoneal dialysis, through a research carried out by literature review, having as a means of theoretical foundation the most relevant and current scientific articles available online on the topic addressed. The mechanism of hemodialysis and peritoneal dialysis is basically by exchange of solutes by the concentration gradient, the waste left by the malfunction of the kidneys are drained from the blood or peritoneal space to the dialysate, a solution prepared to purify the blood/peritoneal fluid. Early diagnosis is extremely important, the kidneys are vital organs and are part of a complex that works to maintain the body's hemostasis.